2000
DOI: 10.1007/s002100000284
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of I Ks channels by HMR 1556

Abstract: Chromanol HMR 1556 [(3R,4S)-(+)-N-[3-hydroxy-2,2-dimethyl-6-(4,4,4-trifluorobutoxy)chroman-4-yl]-N-methylmethanesulfonamide], a novel inhibitor of the slow component of the delayed outward current in heart muscle cells (IKs), has been characterized in several in-vitro systems. mRNA encoding for the human protein minK was injected into Xenopus oocytes, leading to the expression of IKs channels. HMR 1556 inhibited this current half-maximally at a concentration of 120 nmol/l (IC50). Expression of the K+ channels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 22 publications
5
61
0
Order By: Relevance
“…Concentrationresponse studies on I Ks tails ( Figure 2B) confirmed that HMR 1556 is a more potent I Ks blocker than 293B. 10,11 During AP recordings with high-resistance microelectrodes under baseline conditions, AP configurations remained unaltered at 3 and 10 mol/L 293B, but a slight loss of the notch occurred at 30 mol/L, consistent with I to inhibition. 13 Complete loss of the notch, triangulation of the AP, and aspecific APD responses were observed at 100 mol/L.…”
Section: Ks Block By Hmr 1556 and 293bmentioning
confidence: 65%
See 1 more Smart Citation
“…Concentrationresponse studies on I Ks tails ( Figure 2B) confirmed that HMR 1556 is a more potent I Ks blocker than 293B. 10,11 During AP recordings with high-resistance microelectrodes under baseline conditions, AP configurations remained unaltered at 3 and 10 mol/L 293B, but a slight loss of the notch occurred at 30 mol/L, consistent with I to inhibition. 13 Complete loss of the notch, triangulation of the AP, and aspecific APD responses were observed at 100 mol/L.…”
Section: Ks Block By Hmr 1556 and 293bmentioning
confidence: 65%
“…For studies in conscious dogs (6 beagle dogs and 4 mongrel dogs), aliquots of the selective I Ks blocker HMR 1556 10,11 were suspended in 0.5% hydroxyethylcellulose or packed in gelatin capsules and fed to the animals in the morning after overnight fasting. ECG monitoring was done with 24-hour Holter recordings or with telemetry transmitters and a computerized acquisition system (Data Science Inc).…”
Section: In Vivo Studies With Hmr 1556mentioning
confidence: 99%
“…The magnitude of APD prolongation with chromanol 293b was increased in guinea pig papillary muscle and dog Purkinje fiber in the presence of isoproterenol (Schreieck et al, 1997;Han et al, 2001). HMR1556 prolonged APD in vitro in guinea pig papillary muscle in a frequency-independent manner, again with APD prolongation increased in the presence of isoproterenol (Gogelein et al, 2000). In dog left ventricular epicardial, mid-myocardial, and endocardial tissues, exposure to chromanol 293b produced a homogeneous frequency-independent prolongation in APD (Burashnikov and Antzelevitch, 2000).…”
Section: Discussionmentioning
confidence: 86%
“…These are the chromanols exemplified by compound 293b and HMR1556 (Busch et al, 1996;Gogelein et al, 2000), and the benzodiazepines L-735821 and L-768673 ( Fig. 1) (Salata et al, 1996b;Selnick et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…1A). Moreover, HMR-1556 (0.1-100 M), another specific inhibitor of KCNQ1-type K ϩ channels (15,17,32), also inhibited the ZG K ϩ conductive pathway with a similar potency (data not shown). When K ϩ is used as the major osmolyte, both K ϩ -selective and a nonselective monovalent cation permeability pathway contribute to overall ZG lysis (49).…”
Section: Differential Inhibition Of Zg Ion Conductive Pathways By Chrmentioning
confidence: 89%